Smoking Cessation: Barriers, Motivators and the Role of Physicians — A Survey of Physicians and Patients - Veena Joshi PhD; Viranak Suchin PhD; Jeremy Lim MBBS, MBH, MRCS (Edin) (Proceedings of Singapore Healthcare, 2010)
Objective: To identify the motivators of and barriers to smoking cessation and to evaluate the dynamics of the patient-physician visit. Methods: A total of 175 physicians and 347 patient-smokers completed a written questionnaire about their attitudes and behaviours toward smoking cessation. Physicians were additionally queried on their level of involvement in the smoking cessation efforts of their patients. Results: Patient smokers had an average age of 42 years and had been smoking for 15 years. Males and females smoked 17 and 8 cigarettes a day respectively. About 50% of the subjects had made 2–5 attempts to quit smoking in the past and one-third of the subjects had tried to quit once. The top 2 motivators to quit smoking citied by both smokers and physicians were concern about their own health and concern about the health of family members and friends. The third reason given by patient-smokers was the cost of cigarettes. Physicians felt it was their advice that had persuaded/convinced patient-smokers to quit. Both physicians and patient-smokers agreed that the key barriers to smoking cessation were craving/physical addiction and smokers' concern of withdrawal symptoms if they attempted quitting. While both physicians and patients identified similar barriers to smoking cessation, there was a difference in perception about the role physicians play: 55% of physicians said that they discussed smoking cessation with their patients, but only 15% of the patients agreed with this statement. In addition, 78% of physicians said they started the initial discussion while 63% of patient-smokers said they themselves started the initial discussion. Conclusion: Smokers and physicians identified similar motivators of and barriers to smoking cessation. However, there were differences in perception over the roles physicians play.